The dynamic of linkages of Islamic REITs in mixed-asset portfolios in Malaysia. (1st September 2016) - Rozman, Ahmad Tajjudin; Razali, Muhammad Najib; Azmi, Nurul Afiqah; Ali, Hishamuddin Mohd.
Abstract: Islamic REIT (I-REITs) were introduced to the Malaysian stock market approximately ten years ago. This paper assesses dynamic linkages by using the Granger causality test of I-REITs. The study period is from 2008 to 2014. The study concentrates on comparisons between I-REITs and conventional REITs (C-REITs) and provides a better overview of comparisons and linkages of both asset classes. A Cointegration Test determined that a mixed-asset portfolio is cointegrated and shows less diversification benefits between the mixed-asset portfolios. The Granger causality test results has identified that industry portfolio can cause Granger I-REITs' returns to change. This further confirms that I-REITs have good potential to diversify within any asset classes, including shares and bonds.